Rio Birth Cohort Study on Environmental Exposure and Childhood Development – PIPA Project. Issue 1 (11th June 2020) - Asmus, Carmen Ildes R. Fróes; Barbosa, Arnaldo Prata; Meyer, Armando; Damasceno, Nataly; Rosa, Ana Cristina Simões; Medronho, Roberto; da Cunha, Antônio Jose Ledo A.; Moreira, Josino Costa; Fernandes, Thatiana V. R. de B.; Martins, Marlos; Luiz, Ronir Raggio; de Magalhães Câmara, Volney
Background/Objective: As a developing country, Brazil presents a wide range of environmental risks that can constitute hazards to child health. The country also presents different socio-economic-cultural conditions that could be responsible for determining different vulnerability and susceptibility levels for the population, which can potentiate the effects of the environmental pollutants. The Rio Birth Cohort Study (PIPA project) is a prospective maternal-infant health study, hosted in the city of Rio de Janeiro (Southeastern Brazil), designed to investigate separate and combined effects of environmental chemical pollutants, as well as the interactions between these exposures and sociocultural environment and epigenetic patterns. This paper presents the learned lessons and strategies to address the shortcomings detected from this pilot study. Methods: The study population will be all children born at the Federal University of Rio de Janeiro Maternity Hospital from July 1st, 2020 to June 30th, 2021. The estimated population is of 2, 500 children. The study will collect social, demographic, and health information from pregnant women and their children up to four years of age. Biological samples from both mothers and newborns will be collected to assess metal, pesticide and plasticizer exposure. All newborns will have their landmarks of physical, neurological, psychological, and cognitive development recorded at specific ages. Findings: A pilot study was carried out between September 2017 and August 2018, totaling 142 enrolled pregnant women, leading to 135 (95%) births and the collection of umbilical cord (126–93%, ) and mother (139–98%) blood samples, as well as both mother (142–100%) and newborn (54–40%) urine samples and newborn meconium samples (117–86.7%). Conclusions: The study proposes a comprehensive assessment of pre- and postnatal exposure to environmental chemicals at multiple time points in a population living in a highly urbanized developing country. As far as we know, this is the only birth cohort in Brazil specifically designed for this purpose.